2020
DOI: 10.1002/admt.201901085
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive, Selective, Stable, and Flexible NO2 Sensor Based on GaSe

Abstract: Air pollution is a global problem, which poses serious environmental concerns and health risks. In light of this, a key aspect of the challenge of managing air pollution is effective monitoring, which requires reliable high‐sensitivity sensors with strong selectivity and long‐term stability. Layered materials represent an emergent class of materials with extraordinary electronic properties and physicochemical properties, and, therefore, are a highly attractive prospect for this field. Here, such a sensor for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Two-dimensional (2D) materials offer an extremely high surface-to-volume ratio, a layer-dependent electronic structure, and tunable active sites for redox reactions, making them attractive candidates for gas sensing applications. , While they have been widely used for gas sensing applications with an excellent sensitivity for toxic gases such as NO 2 , the reported ultrathin NO 2 sensors usually suffer from slow recovery kinetics at room temperature, inferior selectivity, and/or poor stability. For example, graphene and MoS 2 , have shown excellent sensitivities toward NO 2 , but they are not selective and suffer from slow recovery kinetics.…”
mentioning
confidence: 99%
“…Two-dimensional (2D) materials offer an extremely high surface-to-volume ratio, a layer-dependent electronic structure, and tunable active sites for redox reactions, making them attractive candidates for gas sensing applications. , While they have been widely used for gas sensing applications with an excellent sensitivity for toxic gases such as NO 2 , the reported ultrathin NO 2 sensors usually suffer from slow recovery kinetics at room temperature, inferior selectivity, and/or poor stability. For example, graphene and MoS 2 , have shown excellent sensitivities toward NO 2 , but they are not selective and suffer from slow recovery kinetics.…”
mentioning
confidence: 99%
“…It is noteworthy that the LOD toward NO 2 of our devices is the lowest among the reported self‐powered gas sensors, which might be owing to the excellent intrinsic gas sensing properties of MoS 2 and GaSe. [ 16 , 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Wu et al reported a GaSe-based NO 2 gas sensor at room temperature with the LOD of 0.5 ppb. [16] Wang et al fabricated a self-powered photodetector based on GaSe/WS 2 heterojunction which showed high photoresponsivity and quite short response time. [17] To the best of our knowledge, the heterojunction combining GaSe with other 2D materials as gas sensor has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…A GaSe-based sensor with strong selectivity and long-term stability was fabricated to detect NO 2 . 118 The sensitivity of this sensor was 0.5 ppb at room temperature and its NO 2 selectivity ratio was 100 times that of other interfering environmental gases. In practical terms, GaSe-based sensors can detect vehicle exhaust emissions and act as wearable NO 2 sensors.…”
Section: Schottky-contacted Gas Sensorsmentioning
confidence: 90%